Impact of mAb-induced A475V substitution on viral fitness and antibody neutralization of SARS-CoV-2 omicron variants in the presence of monoclonal antibodies and human convalescent sera - Viriyakitkosol, Ratchanont; Wanitchang, Asawin; Srisutthisamphan, Kanjana; Saenboonreung, Janya; Boonkrai, Chatikorn; Pisitkun, Trairak; Jongkaewwattana, Anan (Frontiers in Immunology, 2023)
The emergence and rapid evolution of SARS-CoV-2 variants have posed a major challenge to the global efforts to control the COVID -19 pandemic. In this study, we investigated the potential of two SARS-CoV-2 variants, BA.2 and BA.5, to evade neutralization by a human monoclonal antibody targeting the virus's spike RBD (mAb 1D1). By subjecting the viruses to serial propagation in the presence of the antibody, we found that BA.2 exhibited poor growth, whereas BA.5 regained robust growth with significantly higher kinetics than the parental virus. Genetic analysis identified a single mutation, A475V, in the spike protein of BA.5 that substantially reduced the neutralizing activities of monoclonal antibodies and convalescent sera. In addition, the A475V mutation alone in BA.2 moderately reduced the neutralizing activity but completely abolished the neutralizing effect of mAb 1D1 when F486V or L452R were also present. Our results shed light on the possible evolutionary development of SARS-CoV-2 variants under selection pressure by monoclonal antibodies and have implications for the development of effective antibody therapies and vaccines against the virus.